(3efXeI GdJLGQI GdYGdejI h JMQjQ GdJLGQI GdOhdjIs - (3eMeO UahJ(B, (3bGHds ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2009)
(3JMQjQ GdJLGQI GdOhdjI h JWhQ GJaGbjGJ gPG GdJMQjQ , efXeI GdJLGQI GdYGdejI , GdOhd GdYQHjI h efXeI GdJLGQI GdYGdejI , GJaGbjGJ efXeI GdJLGQI GdYGdejI aj eLGd GdSdY , GdeDJeQGJ GdhRGQjI defXeI GdJLGQI GdYGdejI , fJGFL JMQjQ JLGQI GdSdY , GJaGbjI JMQjQ JLGQI GdNOeGJ , JMQjQ GdNOeGJ GdeGdjI h Mbhb GdedcjI GdacQjIs
Keywords: (3GdJLGQI GdOhdjIs; (3efXeI GdJLGQI GdYGdejIs